Biomimetic Ambient‐Pressure‐Dried Aerogels with Oriented Microstructures for Enhanced Electromagnetic Shielding - Zhang, Yu‐Chuan; Ding, Rong; Su, Peng‐Gang; Zeng, Fu‐Rong; Jia, Xu‐Xu; Hu, Zai‐Yin; Wang, Yu‐Zhong; Zhao, Hai‐Bo (Advanced functional materials, 2025)
Oriented aerogels, emerging as a new generation of lightweight electromagnetic interference (EMI) materials, often face complex synthesis processes. While creating an orderly oriented microstructure for EMI aerogels through ambient pressure drying (APD) shows promise, it remains a significant challenge. Here, inspired by the directional grown structure of the plant, a new strategy that employs rapid precursor orientation followed by slow cross‐linking to achieve the APD of directional EMI aerogels is proposed. This approach demonstrates that low‐temperature oriented polymerization of polyaniline enables strong cross‐linking with poly(3,4‐ethylenedioxythiophene) and alginate, forming a robust conductive directional skeleton and mitigating surface tension issues during mild drying. The resulting aerogel features high conductivity (48.84 S m−1), excellent flame retardancy, and impressive compressive strength. Notably, its sturdy frame allows for further enhancement with other functional materials, such as Mxene, through re‐processing and re‐drying. The tree‐branch‐like aerogel achieves a significantly improved EMI shielding effectiveness of 50.3 dB across an ultrawideband range of 8.2–40 GHz. This strategy offers a new idea for the straightforward preparation of functional aerogels with programmability and oriented microstructures using ambient drying. Inspired by the directional growth of plants, an ambient‐pressure‐dried strategy to synthesize electromagnetic interference aerogels with oriented microstructures is demonstrated. Low‐temperature polymerization of polyaniline enables cross‐linking with poly(3,4‐ethylenedioxythiophene) and alginate, forming a robust conductive directional skeleton and mitigating surface tension during drying. The aerogel is redryable and reprocessable, achieving an impressive shielding effectiveness across an ultrawideband range.